Acupuncture Needle‐Based Transistor Neuroprobe for In Vivo Monitoring of Neurotransmitter. Issue 52 (7th November 2022) - Zhou, Ying; Liu, Binzhu; Lei, Yongmin; Tang, Lina; Li, Tingxian; Yu, Shanshan; Zhang, Guo‐Jun; Li, Yu‐Tao
Abstract: Chemical communication via neurotransmitters is central to brain functions. Nevertheless, in vivo real‐time monitoring of neurotransmitters released in the brain, especially the electrochemically inactive molecules, remains a great challenge. In this work, a novel needle field‐effect transistor (FET) microsensor based on an acupuncture needle is proposed, which is demonstrated to be capable of real‐time monitoring dopamine molecules as well as neuropeptide Y in vivo. The FET microstructure is fabricated by successively wrapping an insulating layer and a gold layer on the top of the needle, where the needle and the Au served as the source and drain, respectively. After assembling reduced graphene oxide (RGO) between the source and drain electrodes, the specific aptamer is immobilized on the RGO, making this needle‐FET biosensor highly selective and sensitive to real‐time monitor neurotransmitters released from rat brain, even in a Parkinson's diseases model. Furthermore, the needle‐FET biosensor is applied to detect a variety of targets including hormones, proteins, and nucleic acid. By constructing a FET sensing interface on an acupuncture needle and implanting the sensor in a rat's brain for in vivo detection, this work provides a new sight in the FET domain and further expands the species of real‐time in vivo detection. Abstract : Chemical communication via neurotransmitters plays a central role in the brain. Nevertheless, techniques for recording neurochemical signals in vivo are still limited. Here, the fabrication of a novel needle field‐effect transistor biosensor based on an acupuncture needle which is capable of real‐time monitoring neurotransmitters released in vivo is shown.